DEVELOPING HOSPITALITY E-MODULE TO IMPROVE HOTEL EMPLOYEES ENGLISH SKILL - Sherly Franchisca; Khidayatul Munawwaroh; Efa Silfia; Sadjiran Sadjiran; Eka Melati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Abstract The purpose of this research was to develope Hospitality e-modul for hotel, especially for Grand Zuri Hotel Padang employees. The type of this research is Research and Development toward designing and developing e-modul for teaching and learning at Grand Zuri Hotel Padang. It is conducted for the employees of the hotel which participates for English class. In additon, there were 60 (sixty) employees involved in English teaching and learning process at Grand Zuri Hotel Padang which divided into two meeting. In fact, the result of the study shows that: (1) current analysis about teaching and learning process of Grand Zuri Hotel Padang related to several information of the previous teaching and learning process where the learners are in pre-intermediate level and a meeting last in 120 minutes, but there was no modul for the learners; (2) need analysis showed that the dominant skill needed by the learners based on the questionnaire were listening and speaking, generally the ability of the learners in English are good, and there were 19 (nineteen) topics that could be choosen by the learners; (3) in designing and developng e-modul, there were 14 (fourteen) topics in the modul and there was also a syllabus of the modul, also the activity in the e-modul consist of the introduction about the topic, expressions, reading, paired practice, chit chatting, and worksheet; (4) to validate the modul, there were 4 (four) validators involved, General Manager of Grand Zuri Hotel Padang (Surni Yanti,S.Pd), two lecturers from Hotel Management Study Program at Universitas Negeri Padang, and experience trainer for English in hotel industry. In conclusion, based on the findings, there should be attractive and easy to understand materials or e-modul for the employees of Grand Zuri Hotel Padang; (5) in order to know the effectifity of e-modul in teaching and learning there was limited try out in Grand Zuri Hotel. Based on the result of the try out, there is a conclution that the material which is prepared for the employees were needed in teaching and learning process , such as handout, which is made by easy and understandable format to be learned.